2014
DOI: 10.1007/s12053-014-9305-3
|View full text |Cite
|
Sign up to set email alerts
|

Urban energy consumption and CO2 emissions in Beijing: current and future

Abstract: The POL scenario presents a more optimized energy structure compared with the BAU scenario, with the decrease of coal consumption and the increase of natural gas consumption. (4) The commerce and service sector and the energy conversion sector will become the largest contributor to energy consumption and CO2 emissions, respectively. The transport sector and the industrial sector are the two most potential sectors in energy savings and carbon reduction. In terms of sub-scenarios, the TEC is the most effective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 29 publications
1
15
0
2
Order By: Relevance
“…Despite some fluctuations, the energy-related CO 2 emissions of Beijing have stabilized at approximately 100-110 Mt yr -1 (including urban and rural household consumption). Additionally, the declining trend of the secondary industrial sector's carbon emissions has been reported in some studies [1,3,5].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite some fluctuations, the energy-related CO 2 emissions of Beijing have stabilized at approximately 100-110 Mt yr -1 (including urban and rural household consumption). Additionally, the declining trend of the secondary industrial sector's carbon emissions has been reported in some studies [1,3,5].…”
Section: Introductionmentioning
confidence: 93%
“…Detailed direct GHG emission inventories concerning different sources of carbon have been presented. The trends and driving forces have been discussed [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, these results implied that economic growth may be stunted by energy conservation policies. Yu et al [30] tried to estimate the energy consumption and CO 2 emissions in Beijing over the years 2012 to 2030 by developing a model called the "Long-range Energy Alternatives Planning System (LEAP)-BJ model." The study was analyzed based on the Business-as-Usual scenario (BAU) and Policy scenario (POL) scenarios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, climate change is damaging the environments around us , and cities have become the centres of people's social-economic lives (Yu et al 2015). More than 3.6 billion people live in cities (Gouldson et al 2015), and urban populations will pass 6.7 billion in 2050 (UNDESA 2014).…”
Section: Introductionmentioning
confidence: 99%